(untitled) (Journal of Rashid Latif Medical College, 2024)
Background: Throughout human history, education has been a vital institution in every society. It has significantly contributed to the global migration of nations. In all educational institutions across the globe, teachers are tasked with the mental, physical, and moral upbringing of their students, making them the pivot around which global education revolves. The most significant role in the educational process is that of the teacher. Objective: The purpose of this study is to understand the satisfaction of job in teachers. Methodology: This is a qualitative exploratory study. The investigator chose a range of publications and records pertaining to teachers' job satisfaction. Its goal is to capture the intricacy, richness, and background information of the topic being studied. The study reveals underlying meanings, social processes, and theoretical explanations that can improve our comprehension of the elements that contribute to teachers' feeling more satisfied in their jobs. Conclusion: It's critical to comprehend the elements influencing teachers' job happiness in order to promote a pleasant workplace culture and raise the standard of education in general. The subject matter and grade level taught, together with teaching experience, can influence how environmental, personal, and organizational factors affect job satisfaction. However, based on personal preferences and contextual variations, these characteristics' relative relevance may change. It is imperative that educational institutions customize their approaches to improve job satisfaction by taking into account the unique demands and attributes of their faculty. Keywords: Job Satisfaction, Organizational Factors, Environmental Factors, Personal Factors.